2007
DOI: 10.1158/1078-0432.ccr-06-2401
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic versus Chromosomal Prognostic Markers and Clinical Outcome in Uveal Melanoma

Abstract: Purpose:To compare a gene expression^based classifier versus the standard genetic prognostic marker, monosomy 3, for predicting metastasis in uveal melanoma. Experimental Design: Gene expression profiling, fluorescence in situ hybridization (FISH), and array comparative genomic hybridization (aCGH) were done on 67 primary uveal melanomas. Clinical and pathologic prognostic factors were also assessed. Variables were analyzed by Cox proportional hazards, Kaplan-Meier analysis, sensitivity, specificity, positive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
131
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 21 publications
2
131
1
3
Order By: Relevance
“…It has been reported that microRNA signatures differentiate melanoma subtypes; seven microRNAs (microRNA-142-3p, microRNA-486, m ic roR NA-214, m ic roR NA-218, m ic roR NA-362, microRNA-650 and microRNA-31) significantly correlated with acral melanoma compared to non-acral melanoma (15). Furthermore, let-7b and microRNA-199a were upregulated in uveal (ocular) melanoma, showing highly significant associations with the high metastatic gene expression signature and loss of chromosome 3, which have been shown to be more accurate predictors of metastasis than any clinical or pathological factors, and have served as surrogate endpoints for the identification of biomarkers in uveal melanoma (16)(17)(18). Similar findings have been found in both skin melanoma and uveal (ocular) melanoma, but it is unclear as to whether this finding is coincidental or whether it is an important indicator of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that microRNA signatures differentiate melanoma subtypes; seven microRNAs (microRNA-142-3p, microRNA-486, m ic roR NA-214, m ic roR NA-218, m ic roR NA-362, microRNA-650 and microRNA-31) significantly correlated with acral melanoma compared to non-acral melanoma (15). Furthermore, let-7b and microRNA-199a were upregulated in uveal (ocular) melanoma, showing highly significant associations with the high metastatic gene expression signature and loss of chromosome 3, which have been shown to be more accurate predictors of metastasis than any clinical or pathological factors, and have served as surrogate endpoints for the identification of biomarkers in uveal melanoma (16)(17)(18). Similar findings have been found in both skin melanoma and uveal (ocular) melanoma, but it is unclear as to whether this finding is coincidental or whether it is an important indicator of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Starting a little over a decade ago, investigators around the world began to report that chromosomal and transcriptional features of primary uveal melanoma cells were strongly associated with the pa tient's likelihood of developing subsequent extraophthalmic metastasis and metastatic death (25,(29)(30)(31)(32)(33)(34)(35) Several authors have shown that these chromosomal and transcriptional features can be determined on tumor specimens obtained by FNAB changing the indication for FNAB from purely diagnostic to investigational-prognostic (24,25,(36)(37)(38) . During the past few years, investigators from several of these centers have reported their experience with cytogenetic testing of the obtained FNAB aspirates (25,27,35,37,(39)(40)(41) .…”
Section: Prognostic Implications Of Cytopathologic Classification Of mentioning
confidence: 99%
“…12,24,25 Such an analysis can be performed by charting chromosomal alternations 26,27 or by gene expression profiling. 24,25,28 The latest TNM edition encourages recording of genetic features. 9 A major breakthrough was the observation that many uveal melanomas lack one copy of chromosome 3, and that these monosomic tumours are usually those that metastatise.…”
Section: Prognosis Of the Primary Tumourmentioning
confidence: 99%